Wire rods, steel wires, and machine parts

The use of a bainite-dominated microstructure in wire rods and steel wires with controlled chemical composition enhances strength and formability, addressing mold damage and elongation issues in non-thermal bolts, ensuring high 0.2% yield strength without bluing treatments.

JP7610174B1Active Publication Date: 2025-01-08NIPPON STEEL CORPORATION

Patent Information

Application Number
JP2024544538
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-03-31
Filing Date
2024-03-29
Publication Date
2025-01-08
Estimated Expiration
2044-03-29

AI Technical Summary

Technical Problem

Conventional non-thermal bolts made from steel wire rods face issues such as mold damage, high dislocation density leading to low 0.2% yield strength, and large permanent elongation, making them difficult to apply to high-strength bolts without additional heat treatments like bluing.

Method used

A wire rod and steel wire composition with specific chemical elements and a bainite-dominated microstructure, optimized to achieve a high 0.05% proof stress ratio and controlled hardness variation, enabling high 0.2% proof stress and suppressed permanent elongation without bluing treatment.

Benefits of technology

The solution results in wire rods and steel wires with excellent strength and formability, achieving high 0.2% yield strength and reduced permanent elongation, even without post-forming heat treatments, thereby improving the durability and processability of mechanical parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007610174000006
    Figure 0007610174000006
  • Figure 0007610174000007
    Figure 0007610174000007
  • Figure 0007610174000001
    Figure 0007610174000001
Patent Text Reader

Abstract

A wire having a specified chemical composition, in which when the diameter of the wire is D, the metal structure at a 1 / 4D portion, which is 1 / 4D deep from the surface of the wire in a cross section perpendicular to the longitudinal direction of the wire, contains bainite by area ratio of 70% or more, and when the C content in mass% is (C%), the ratio of 0.05% proof stress to tensile strength (0.05% proof stress / tensile strength) is 0.72-0.40 x (C%) or more, and the value obtained by dividing the standard deviation of Vickers hardness in a cross section perpendicular to the longitudinal direction of the wire by the average Vickers hardness is 0.150 or less, and applications thereof.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a wire rod, a steel wire, and a machine part. [Background technology]

[0002] High-strength materials are required for machine parts such as steel bolts and screws in order to reduce their weight and size. Conventionally, these machine parts are manufactured by softening machine structural steel wire rods containing C, Mn, Cr, Mo, etc. through spheroidizing annealing, forming them into a desired shape through cold heading and rolling, and then quenching and tempering to impart strength.

[0003] Because heat treatments such as spheroidizing annealing and quenching and tempering increase manufacturing costs and CO2 emissions, a non-tempered bolt is known that omits these heat treatments and instead uses wire drawing to increase strength after adjusting the composition and rapid cooling. 2. Description of the Related Art Various wire rods and steel wires for producing machine parts such as non-heat treated bolts have been proposed (see, for example, Patent Documents 1 to 6).

[0004] Patent document 1: Japanese Patent Application Laid-Open No. 2-166229 Patent Document 2: International Publication No. 2016 / 121820 Patent Document 3: International Publication No. 2017 / 122830 Patent Document 4: International Publication No. 2018 / 008698 Patent Document 5: JP 2021-183710 A Patent Document 6: Japanese Patent Application Laid-Open No. 3-6325 Summary of the Invention [Problem to be solved by the invention]

[0005] Non-tempered bolts are made by forming steel wire whose strength has been increased by wire drawing. As the strength of the steel wire increases, the mold becomes more susceptible to damage and wear during forming, and the product becomes more susceptible to processing cracks, making it difficult to apply this to high-strength bolts. In addition, conventional non-tempered bolts have a high dislocation density, which means that the 0.2% yield strength of the bolt is low, resulting in a problem of large permanent elongation of the bolt. To improve this, it is necessary to add a bluing process in which the bolt is held at 300 to 400°C after being formed into mechanical parts such as bolts.

[0006] An object of the present disclosure is to provide a wire rod and steel wire for obtaining mechanical components that are excellent in strength and formability, and that can achieve high 0.2% yield strength and suppressed permanent elongation even if a bluing treatment is omitted after molding into the mechanical components, and to provide the mechanical components. [Means for solving the problem]

[0007] The above problems are solved by the following means. <1> In mass%, C: 0.08 to 0.80%, Si: 0.03 to 1.50%, Mn: 0.50-2.00%, P: 0.050% or less, S: 0.050% or less, Al: 0.005 to 0.080%, N: 0.0010~0.0150%, O: 0.003% or less, Ti: 0 to 0.050%, B: 0 to 0.0050%, Cr: 0-1.50%, Mo: 0 to 0.50%, Nb: 0 to 0.050%, V: 0~0.20%, Cu: 0-0.50%, Ni: 0-0.70%, Sn: 0-0.30%, Sb: 0 to 0.005%, and Ca: 0 to 0.0050%, and the balance being Fe and impurity elements, When the diameter of the wire is D, a metal structure at a 1 / 4D portion having a depth of 1 / 4D from the surface of the wire in a cross section perpendicular to the longitudinal direction of the wire contains bainite at an area ratio of 70% or more, When the C content in mass% is (C%), the ratio of 0.05% proof stress to tensile strength (0.05% proof stress / tensile strength) is 0.72-0.40 × (C%) or more; A wire having a standard deviation of Vickers hardness in a cross section perpendicular to the longitudinal direction of the wire divided by the average value of the Vickers hardness of the wire, the standard deviation being 0.150 or less. <2> In mass%, C: 0.08 to 0.80%, Si: 0.03 to 1.50%, Mn: 0.50-2.00%, P: 0.050% or less, S: 0.050% or less, Al: 0.005 to 0.080%, N: 0.0010~0.0150%, O: 0.003% or less, Ti: 0 to 0.050%, B: 0 to 0.0050%, Cr: 0-1.50%, Mo: 0 to 0.50%, Nb: 0 to 0.050%, V: 0~0.20%, Cu: 0-0.50%, Ni: 0-0.70%, Sn: 0-0.30%, Sb: 0 to 0.005%, and Ca: 0 to 0.0050%, and the balance being Fe and impurity elements, When the diameter of the steel wire is d, a metal structure at a 1 / 4d portion having a depth of 1 / 4d from the surface of the steel wire in a cross section perpendicular to the longitudinal direction of the steel wire contains bainite in an area ratio of 70% or more, When the C content by mass is (C%), the tensile strength is 610+900×(C%)MPa or more, the reduction in area is 62-32×(C%)% or more, the tensile strength (MPa)×reduction in area (%) is 52000 or more, and the ratio of 0.2% proof stress to tensile strength (0.2% proof stress / tensile strength) is 0.985-0.083×(C%) or more, A steel wire, wherein a value obtained by dividing the standard deviation of Vickers hardness in a cross section perpendicular to the longitudinal direction of the steel wire by the average value of the Vickers hardness is 0.150 or less. <3> A mechanical part including a shaft portion, In mass%, C: 0.08 to 0.80%, Si: 0.03 to 1.50%, Mn: 0.50-2.00%, P: 0.050% or less, S: 0.050% or less, Al: 0.005 to 0.080%, N: 0.0010~0.0150%, O: 0.003% or less, Ti: 0 to 0.050%, B: 0 to 0.0050%, Cr: 0-1.50%, Mo: 0 to 0.50%, Nb: 0 to 0.050%, V: 0~0.20%, Cu: 0-0.50%, Ni: 0-0.70%, Sn: 0-0.30%, Sb: 0 to 0.005%, and Ca: 0 to 0.0050%, and the balance being Fe and impurity elements, When the diameter of the shaft portion is dm, a metal structure at a 1 / 4 dm portion having a depth of 1 / 4 dm from the surface of the shaft portion in a cross section perpendicular to the longitudinal direction of the shaft portion contains bainite in an area ratio of 70% or more, When the C content in mass% is (C%), the tensile strength of the shaft portion is 580 + 900 × (C%) MPa or more; The ratio of 0.2% proof stress to the tensile strength (0.2% proof stress / tensile strength) is 0.90 or more, A mechanical component, wherein a value obtained by dividing the standard deviation of Vickers hardness in a cross section perpendicular to the longitudinal direction of the shaft portion by the average value of the Vickers hardness is 0.150 or less. Effect of the Invention

[0008] According to the present disclosure, there are provided a wire rod and a steel wire for obtaining mechanical components having excellent strength and formability, and having high 0.2% yield strength and suppressed permanent elongation even when a bluing treatment is omitted after molding into the mechanical components, and a mechanical component. [Brief description of the drawings]

[0009] [Figure 1A] FIG. 2 is a diagram showing an example of an SEM photograph mainly of a bainite structure. [Figure 1B] FIG. 13 is a diagram showing another example of an SEM photograph mainly of a bainite structure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The wire according to the present disclosure will now be described. In this disclosure, a numerical range expressed using "~" means a range that includes the numerical values ​​before and after "~" as the lower and upper limits. However, when the numerical values ​​before and after "~" are followed by "more than" or "less than," the numerical range does not include these numerical values ​​as the lower or upper limit. The content of an element in a chemical composition may be expressed by adding the "amount" to the element symbol (for example, C amount, Si amount, etc.). With respect to the contents of elements in chemical compositions, "%" means "mass %." When the content of an element in a chemical composition is described as "0~", it means that the element does not have to be contained. The term "process" includes not only an independent process but also a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process is achieved. The "surface" of a wire means the "outer peripheral surface." The "central axis" of a wire means an imaginary line that passes through the center point of a cross section perpendicular to the longitudinal direction of the wire and extends in the longitudinal direction (axial direction). "1 / 4D" is synonymous with "D / 4".

[0011] The inventors of the present disclosure have studied the effects of the structure and mechanical properties of a wire rod on the characteristics of steel wire and mechanical parts after wire drawing, and have found that by setting the components of the wire rod within a specific range, making the structure of the wire rod mainly bainite with the area ratios of ferrite, pearlite, and martensite suppressed, and further setting the ratio of the tensile strength and 0.05% yield strength of the wire rod, i.e., 0.05% yield strength / tensile strength (hereinafter referred to as the "0.05% yield strength ratio of the wire rod") within a specific range, and further reducing the standard deviation of the hardness of the wire rod, it is possible to obtain a steel wire with excellent strength and formability after wire drawing, and a high 0.2% yield strength ratio (0.2% yield strength / tensile strength) and suppression of permanent elongation of the bolt after processing into a non-tempered bolt.

[0012] When the structure of the wire rod is mainly ferrite or pearlite, the 0.2% yield strength ratio of the bolt is small. Non-tempered bolts have a high dislocation density because their strength is imparted by wire drawing. If there are many mobile dislocations, they will undergo plastic deformation with small strain, lowering the elastic limit and, as a result, reducing the yield strength. In order to increase the yield strength of steel with high dislocation density, it is effective to fix the solute carbon and nitrogen contained in the steel to the dislocations to suppress their movement.

[0013] Conventional non-tempered bolts use a heat treatment called bluing, which involves holding the bolt at 300 to 400°C to fix carbon to the dislocations, suppressing their movement and increasing the bolt's 0.2% yield strength. The inventors of the present disclosure have found that by making the structure of the wire rod mainly bainite and setting the 0.05% proof stress ratio of the wire rod within a specific range, the 0.2% proof stress ratio of the non-tempered bolt is high even without bluing treatment. Wire rods with normal bainite structure have a high mobile dislocation density and therefore a low elastic limit. When solute carbon is fixed to mobile dislocations, the movement of dislocations is suppressed and the elastic limit is high. Since the commonly used 0.2% proof stress is affected by plastic deformation, the present disclosure uses the 0.05% proof stress, which shows a value closer to the elastic limit. Wire rods with bainite structure having a high 0.05% proof stress have a large amount of solute carbon fixed to dislocations. Since the solute carbon is removed from the fixation of dislocations by wire drawing, it is considered that a steel wire drawn from a wire rod with bainite structure having a high 0.05% proof stress has a high solute carbon concentration. It is presumed that a high amount of solute carbon causes carbon to adhere to mobile dislocations, suppressing dislocation movement without the need to heat to the bluing treatment temperature of 300 to 400°C, thereby increasing the 0.2% yield strength ratio of the bolt.

[0014] If the martensite fraction of the wire is high, the wire may break during drawing, or cracks may occur during forming, and the 0.2% yield strength ratio of the bolt may be low. Even if the wire has a bainite-based structure, if the 0.05% yield strength ratio of the wire is low, the 0.2% yield strength ratio of the bolt may be low. The reason for this is that in order to increase the 0.2% yield strength ratio of the bolt, a sufficient amount of solute carbon is required to fix mobile dislocations after drawing, but when the 0.05% yield strength ratio of the wire is low, the 0.2% yield strength ratio of the bolt decreases due to a lack of solute carbon. In addition, the bainite-based structure reduces work hardening, which is suppressed in high-strain processing such as processing of the head of the bolt, and the load on the die is reduced. Furthermore, the bainite structure has split cementite and high ductility, so that work cracks can be suppressed.

[0015] If the hardness of the wire varies widely, the 0.2% yield strength ratio of the bolt after forming decreases. In addition, processing cracks are more likely to occur during bolt forming. The reason for this is believed to be that the deformation caused by wire drawing becomes uneven, which in turn causes the distribution of dislocations to become uneven.

[0016] <Wire rod> The wire rod according to the present disclosure has been discovered based on the above findings. The chemical composition, metal structure, mechanical properties, and manufacturing method of the wire rod according to the present disclosure will be described below.

[0017] [Chemical composition] The chemical composition of the wire according to the present disclosure is, as essential elements, in mass%: C: 0.08 to 0.80%, Si: 0.03 to 1.50%, Mn: 0.50-2.00%, P: 0.050% or less, S: 0.050% or less, Al: 0.005 to 0.080%, and N: 0.0010~0.0150%, O: Contains 0.003% or less, with the balance being Fe and impurity elements. The wire according to the present disclosure may contain other optional elements as necessary.

[0018] C: 0.08 to 0.80% C is contained to ensure the strength required for mechanical parts. If the C content is less than 0.08%, it is difficult to ensure the necessary strength for mechanical parts. On the other hand, if the C content exceeds 0.80%, ductility, toughness, and cold forgeability deteriorate. Therefore, the C content is set to 0.08 to 0.80%. The lower limit of the C content is 0.08%, preferably 0.15%, and more preferably 0.20%, and the upper limit of the C content is 0.80%, preferably 0.75%, and more preferably 0.70%. The preferred C content for achieving high strength, ductility, toughness, and cold workability is 0.15 to 0.75%, and more preferably 0.20 to 0.70%.

[0019] Silicon: 0.03 to 1.50% Silicon functions as a deoxidizing element and is an effective element for imparting necessary strength to mechanical components. If the amount of silicon is less than 0.03%, these effects are insufficient. If the amount of silicon exceeds 1.50%, the ductility and toughness of the mechanical components deteriorate, and the deformation resistance of the steel wire increases, deteriorating the cold forgeability. Therefore, the amount of silicon is set to 0.03 to 1.50%. The amount of silicon is preferably 0.05 to 1.00%, and more preferably 0.10 to 0.60%.

[0020] Mn: 0.50-2.00% Mn is an element necessary to impart necessary strength to mechanical parts. If the Mn content is less than 0.50%, the effect is insufficient. If the Mn content exceeds 2.00%, the toughness of the mechanical parts is deteriorated, and the deformation resistance of the steel wire increases, deteriorating the cold forgeability. Therefore, the Mn content is set to 0.50-2.00%. The Mn content is preferably 0.70-1.50%, and more preferably 0.90-1.20%.

[0021] P:0.050% or less P is contained in the wire rod as an impurity. It is desirable to reduce P content because P segregates at the grain boundaries of mechanical components and deteriorates toughness. For this reason, the upper limit of P content is set to 0.050%. A preferable upper limit of P content is 0.020%, and a more preferable upper limit is 0.015% or less. The lower limit of P content is preferably 0% (i.e., no P content), but may be more than 0% (or 0.0001% or more) from the viewpoint of reducing the dephosphorization cost.

[0022] S: 0.050% or less S is contained in the wire rod as sulfides such as MnS. If the S content exceeds 0.050%, the cold heading property of the steel wire is deteriorated and the toughness of the mechanical parts is deteriorated. Therefore, the upper limit of the S content is set to 0.050%. A preferable upper limit of the S content is 0.030%. A more preferable upper limit is 0.015%. Note that the lower limit of the S content may be more than 0% (or 0.001% or more) from the viewpoint of reducing the desulfurization cost.

[0023] Al: 0.005 to 0.080% Al functions as a deoxidizing element, and also has the effect of forming AlN to refine crystal grains and improve the toughness of mechanical parts. It also has the effect of fixing solute N, suppressing dynamic strain aging, and reducing deformation resistance. If the Al content is less than 0.005%, these effects are insufficient. If the Al content exceeds 0.080%, the effects become saturated and manufacturability may decrease. Therefore, the Al content is set to 0.005 to 0.080%. The Al content is preferably 0.010 to 0.065%, and more preferably 0.020 to 0.055%.

[0024] N: 0.0010~0.0150% N forms nitrides with Al, Ti, Nb, V, etc., refines crystal grains, and has the effect of improving the toughness of mechanical parts. If the N content is less than 0.0010%, the amount of nitrides precipitated is insufficient, and the effect cannot be obtained. If the N content exceeds 0.0150%, the deformation resistance of the steel wire increases due to dynamic strain aging caused by solute N, and the workability deteriorates. Therefore, the N content is set to 0.0010 to 0.0150%. The N content is preferably 0.0020 to 0.0100%, and more preferably 0.0025 to 0.0060%.

[0025] O: 0.003% or less O is an impurity and is inevitably contained in steel. If the O content exceeds 0.003%, coarse oxides are formed, which may reduce fatigue strength, so the O content is limited to 0.003% or less. The preferred upper limit of the O content is 0.002%.

[0026] Remainder: Fe and impurity elements In the chemical composition of the wire according to the present disclosure, the balance is Fe and impurity elements (which may be referred to as "impurities" as appropriate in the present disclosure). Here, the term "impurities" refers to components contained in raw materials or components mixed in during the manufacturing process and not intentionally added. Furthermore, impurities also include components that are intentionally added but are contained in an amount that does not affect the performance of the steel wire obtained by drawing the wire rod according to the present disclosure.

[0027] Furthermore, the wire rod according to the present disclosure may contain, in mass %, one or more elements selected from the group consisting of the following Groups A to D, instead of a portion of Fe. Note that the elements in the following Groups A to D are optional elements, and these elements may not be included, i.e., may be 0%.

[0028] [Group A] Ti: 0.050% or less, and B: 0.0050% or less of one or two selected from the group consisting of

[0029] Ti: 0.050% or less Ti functions as a deoxidizing element and is effective in facilitating the formation of bainite. If the Ti content exceeds 0.050%, these effects are saturated and coarse oxides or nitrides are formed, which may deteriorate the fatigue strength of the mechanical parts. Therefore, if Ti is contained, the Ti content is preferably 0.002 to 0.050%. The Ti content is preferably 0.003 to 0.050%, and more preferably 0.007 to 0.040%.

[0030] B: 0.0050% or less B has the effect of facilitating the formation of bainite. If the B content exceeds 0.0050%, carbides are formed at the grain boundaries, which may deteriorate the wire drawability. Therefore, when B is contained, the B content is preferably 0.0002 to 0.0050%. The B content is preferably 0.0003 to 0.0050%, and more preferably 0.0008 to 0.0030%.

[0031] [Group B] Cr: 1.50% or less, Mo: 0.50% or less Nb: 0.050% or less, and V: 0.20% or less, one or more selected from the group consisting of

[0032] Cr:1.50% or less Cr is an element necessary to impart necessary strength to mechanical parts. If the Cr content exceeds 1.50%, the martensite fraction of the wire rod increases, deteriorating wiredrawability, and increasing the deformation resistance of the steel wire, deteriorating cold forgeability. Therefore, the Cr content is set to 1.50% or less. The Cr content is preferably 0.02 to 0.80%, and more preferably 0.10 to 0.50%.

[0033] Mo: 0.50% or less Mo has the effect of imparting necessary strength to mechanical parts. If the Mo content exceeds 0.50%, the alloy cost increases, and the deformation resistance of the steel wire increases, deteriorating the cold forgeability. Therefore, when Mo is contained, the Mo content is preferably 0.02 to 0.50%. The Mo content is preferably 0.03 to 0.35%, and more preferably 0.05 to 0.25%. The Mo content may be 0.15% or less.

[0034] Nb: 0.050% or less Nb has the effect of increasing the strength of mechanical parts by precipitating carbides and nitrides, the effect of improving toughness by refining crystal grains, the effect of reducing solute N and reducing deformation resistance, etc. If the Nb content exceeds 0.050%, the effect is saturated and the cold forgeability may deteriorate. Therefore, when Nb is contained, the Nb content is preferably 0.002 to 0.050%. The Nb content is preferably 0.001 to 0.040%. The Nb content is more preferably 0.005 to 0.030%.

[0035] V: 0.20% or less V has the effect of precipitating carbides and nitrides to increase the strength of mechanical parts. If the V content exceeds 0.20%, the alloy cost increases. Therefore, if V is contained, the V content should be 0.02 to 0.20%. The preferred V content range is 0.01 to 0.15%.

[0036] [Group C] Cu: 0.50% or less, Ni: 0.70% or less, Sn: 0.30% or less, and Sb: 0.005% or less, one or more selected from the group consisting of

[0037] Cu: 0.50% or less Cu precipitates finely, imparting necessary strength to mechanical parts and improving corrosion resistance. If the Cu content exceeds 0.50%, hot ductility deteriorates and surface defects are likely to occur. Therefore, if Cu is contained, the Cu content should be 0.02 to 0.50%. The preferred Cu content is 0.02 to 0.30%.

[0038] Ni: 0.70% or less Ni has the effect of improving corrosion resistance. If the Ni content exceeds 0.70%, the alloy cost increases. Therefore, when Ni is contained, the Ni content is preferably 0.02 to 0.70%. The Ni content is preferably 0.02 to 0.50%, and more preferably 0.05 to 0.30%.

[0039] Sn: 0.30% or less Sn has the effect of improving corrosion resistance. When Sn is contained, the Sn content should be 0.002% or more. However, if the Sn content exceeds 0.30%, the ductility decreases and the cold workability deteriorates, so the Sn content is limited to 0.30% or less. The preferred upper limit of the Sn content is 0.20%.

[0040] Sb: 0.005% or less Sb has the effect of improving corrosion resistance. When Sb is contained, the Sb content should be 0.001% or more. However, if the Sb content exceeds 0.005%, the ductility decreases and the cold workability deteriorates, so the Sb content is limited to 0.005% or less. The upper limit of the Sb content is preferably 0.004%, and more preferably 0.003%.

[0041] [Group D] Ca:0.0050% or less Ca is contained as a deoxidizing element. Ca has the effect of making oxides finer and improving fatigue strength. If the Ca content exceeds 0.0050%, ductility decreases and cold workability deteriorates, so the Ca content is limited to 0.0050% or less. The preferred upper limit of the Ca content is 0.0040%, and the more preferred upper limit is 0.0030%.

[0042] [Metal structure of wire] Next, the metal structure of the wire according to the present disclosure will be described. In the metal structure of the wire rod according to the present disclosure, the area ratio of bainite at a depth of 1 / 4D from the surface (outer peripheral surface) of the wire rod in a cross section (C cross section) perpendicular to the longitudinal direction of the wire rod is 70% or more. If the area ratio of bainite is less than 70%, the 0.2% proof stress ratio of the mechanical part decreases and the workability deteriorates. The area ratio of bainite is preferably 80% or more, and more preferably 90% or more.

[0043] (Method of measuring metal structure of wire rod) For microstructural observation, two samples are taken from positions 50 mm apart in the axial direction of the wire, the cross section perpendicular to the central axis of each wire sample (C section) is mirror-polished, etched with picral, and the 1 / 4D section is observed. First, the C-section of the wire to be measured is mirror-polished and then etched with picral (a solution of 5% picric acid and 95% ethanol) to reveal the structure. Next, in the 1 / 4D section, four locations are taken at 90° intervals in the circumferential direction, and a region of 20 μm × 20 μm or more at each location is photographed at a magnification of 5000 times using a field emission scanning electron microscope (FE-SEM). Examples of bainite structure are shown in Figures 1A and 1B.

[0044] The metal structure may contain bainite, pearlite, martensite, and ferrite. Of these, martensite and ferrite do not contain carbides within the grains. The pearlite structure is a structure in which cementite and ferrite are alternately arranged almost parallel to each other. Therefore, structures other than bainite (structures that do not contain carbides within the grains, pearlite structures) in the photographed structure are visually marked, and the area of ​​the region of the structure other than bainite is obtained by image analysis (software name: Nireco's small general-purpose image processing analysis system LUZEX_AP). This operation is performed by measuring and calculating two samples, averaging the results, and subtracting the area percentage of the structure other than bainite from the total area (100%) to obtain the area percentage of bainite in this disclosure.

[0045] [Mechanical properties of wire] 0.05% yield strength / tensile strength: 0.72-0.40×(C%) or more In the wire rod according to the present disclosure, the ratio of 0.05% yield strength to tensile strength (0.05% yield strength / tensile strength) is 0.72-0.40×(C%) or more, where (C%) is the C content in mass %. When the 0.05% yield strength / tensile strength is 0.72-0.40×(C%) or more, a high 0.2% yield strength ratio can be obtained after molding into a mechanical part without performing a bluing process. The 0.05% yield strength / tensile strength is preferably 0.78-0.40×(C%) or more.

[0046] The tensile test of wire rod is performed using JIS Z2241:2011 No. 14A test piece according to the test method of JIS Z2241:2011 to measure tensile strength (TS), 0.05% proof stress, and reduction in area. The 0.05% proof stress is the stress when the plastic elongation is 0.05% of the extensometer gauge length according to the offset method defined in JIS Z2241:2011. The tensile test piece is machined and taken from the wire rod immediately after straightening. The tensile test is performed on three samples, and the average value is used.

[0047] (Vickers hardness of wire) The wire rod according to the present disclosure has a value obtained by dividing the standard deviation of Vickers hardness in a cross section (C cross section) perpendicular to the longitudinal direction of the wire rod by the average value of Vickers hardness of 0.150 or less. When this value is 0.150 or less, the 0.2% proof stress ratio of a mechanical part manufactured from the steel wire through wire drawing is high. In addition, the workability when forming into a mechanical part is improved. The value is preferably 0.100 or less, more preferably 0.050 or less.

[0048] The hardness test is carried out by mirror-polishing the C-section of the wire and using a Vickers hardness tester, measuring nine points in total: four points at a depth of 1.0 mm from the surface of the wire, rotated at 90° intervals around the wire, four points at a depth of D / 4 (where D is the diameter of the wire), rotated at 90° intervals around the wire, and one point at the center, and calculating the average value and standard deviation. The measured values ​​are expressed as x1, x2, ...x n Then, the average value X ave and standard deviation s were calculated using the following formula. X ave =(1 / n)×Σx n s = ((1 / n) × Σ(x n -X ave ) 2 ) (1 / 2) The test force for measuring Vickers hardness is 9.8 N, and the measurement is performed according to the method of JIS Z2244-1:2020.

[0049] (Wire diameter) The wire diameter D of the wire according to the present disclosure is not particularly limited, but is preferably 3.0 to 25.0 mm, and more preferably 5.0 to 18.0 mm.

[0050] [Wire rod manufacturing method] An example of a method for producing a wire according to the present disclosure will be described. A steel slab made of the specified components that satisfy the above-mentioned chemical composition is heated to 1100 to 1250°C and held in the furnace for 90 minutes or more. Thereafter, the slab is hot-rolled at an entry temperature of 750 to 800°C for finish rolling, and then coiled into a ring shape at 780 to 820°C. After coiling, the wire is primarily cooled to 750°C at an average cooling rate of 2 to 15°C / s. After that, secondary cooling is performed from 750°C to 500°C at an average cooling rate of 25°C / s or more. Next, the third cooling is performed from 500°C to 450°C at an average cooling rate of 20°C / s or less. The wire is then held at 420-440°C for 30-100 seconds (primary holding), then heated from 490°C to 550°C at an average heating rate of 10°C / s or more, held at 580-620°C for 60-200 seconds (secondary holding), and then water-cooled to obtain the wire.

[0051] If the heating temperature is less than 1100°C or the heating time is less than 90 minutes, the carbide will not be fully dissolved, and the 0.05% yield strength ratio of the wire will decrease. If the heating temperature exceeds 1250°C, the surface hardness of the wire will decrease due to decarburization. If the entry temperature of the finish rolling exceeds 800°C, the gamma grains (austenite grains) become coarse, the ductility of the wire rod decreases, and the workability deteriorates. If the entry temperature is less than 750°C, the gamma grain size becomes non-uniform, and the standard deviation of the hardness of the wire rod increases. If the coiling temperature exceeds 820°C, the gamma grains become coarse, the ductility of the wire rod decreases, and the workability deteriorates.If the coiling temperature is less than 780°C, the area ratio of bainite decreases, and the 0.05% proof stress ratio of the wire rod decreases. After coiling, if the primary average cooling rate to 750°C is less than 2°C / s, the gamma grains become coarse, the ductility of the wire decreases, and workability deteriorates. If it exceeds 15°C / s, the recovery and recrystallization of the gamma grains is delayed, and the grains become mixed. As a result, the gamma grain size becomes non-uniform, the standard deviation of the hardness of the wire increases, and the 0.2% proof stress ratio and permanent elongation of the mechanical parts deteriorate. If the secondary average cooling rate from 750°C to 500°C is less than 25°C / s, the area ratio of ferrite and pearlite increases, and the 0.05% yield strength ratio of the wire rod decreases. When the tertiary average cooling rate from 500 to 450 °C exceeds 20 °C / s, the standard deviation of the hardness of the wire increases, and the formability of the bolt after drawing deteriorates, as well as the 0.2% yield strength ratio and permanent elongation of the bolt. If the first holding time at 420 to 440°C is less than 30 seconds, the hardness of the wire will vary greatly, and the 0.2% yield strength ratio and permanent elongation of the mechanical parts will deteriorate. If the first holding time exceeds 100 seconds, the 0.05% yield strength ratio of the wire will decrease. If the average heating rate from 490°C to 550°C is less than 10°C / s, the 0.05% yield strength ratio of the wire will decrease and the 0.2% yield strength ratio and permanent elongation of the mechanical parts will deteriorate. If the secondary holding temperature is less than 580°C, the 0.2% yield strength ratio and permanent elongation of the mechanical parts will deteriorate, and if it exceeds 620°C, the strength will decrease. If the secondary holding time is less than 60 seconds, the 0.05% yield strength ratio of the wire will decrease. If the secondary holding time exceeds 200 seconds, the carbides will coarsen and the reduction in area of ​​the steel wire after drawing will decrease.

[0052] The wire rod according to the present disclosure is drawn at an area reduction rate of 15 to 50% to form a steel wire, which is then cold heading and rolling processed into the shape of a mechanical part such as a bolt. If the area reduction rate of the wire drawing is less than 15%, the yield strength ratio of the mechanical part decreases and the permanent elongation increases. If the area reduction rate of the wire drawing is 50% or more, the workability of the mechanical part deteriorates. After the wire drawing, galvanization and baking treatment are performed as necessary.

[0053] The steel wire manufactured using the wire rod of the present disclosure has high strength and drawing ability, and is excellent in strength and formability of the bolt. A non-tempered bolt manufactured using such a steel wire has a high bolt 0.2% yield strength ratio and excellent permanent elongation even if the bluing treatment after forming is omitted. The steel wire and the machine component according to the present disclosure will be described below. Note that the chemical composition of the steel wire and the machine component according to the present disclosure is the same as that of the wire rod described above, and therefore will not be described below.

[0054] <Steel wire> The steel wire according to the present disclosure is obtained by wiredrawing the above wire rod, and plastic flow is observed in the surface layer of the longitudinal cross section of the steel wire. The metal structure and mechanical properties of the steel wire according to the present disclosure will be described.

[0055] [Metal structure of steel wire] In the steel wire according to the present disclosure, when the diameter of the steel wire is d, the metal structure at a 1 / 4d portion, which is 1 / 4d deep from the surface of the steel wire in a cross section perpendicular to the longitudinal direction of the steel wire, contains bainite with an area ratio of 70% or more. If the bainite area ratio is less than 70%, the 0.2% proof stress ratio of the mechanical component decreases and the workability deteriorates. The bainite area ratio is preferably 80% or more, and more preferably 90% or more. The metal structure of the steel wire can be measured in the same manner as the metal structure of the wire rod described above.

[0056] [Mechanical properties of steel wire] Tensile strength: 610+900×(C%)MPa or more Aperture: 62-32×(C%)% or more Tensile strength (MPa) x reduction (%): 52000 or more 0.2% yield strength ratio (0.2% yield strength / tensile strength): 0.985-0.083×(C%) or more The steel wire according to the present disclosure has a tensile strength of 610+900×(C%)MPa or more, an area reduction of 62-32×(C%)% or more, a tensile strength (MPa)×area reduction of 52,000 or more, and a 0.2% yield strength ratio (0.2% yield strength / tensile strength) of 0.985-0.083×(C%) or more, where (C%) is the C content by mass. When the tensile strength, reduction in area, and 0.2% yield strength ratio of the steel wire satisfy the above relationships, when a non-tempered mechanical part is manufactured from this steel wire, the cold workability is improved and sufficient strength for the mechanical part is obtained.

[0057] From the viewpoint of achieving both cold workability and tensile strength when made into a mechanical part, it is preferable that the tensile strength is 640+900×(C%)MPa or more, the reduction in area is 66-32×(C%)% or more, tensile strength (MPa)×reduction in area (%) is 53,000 or more, and the 0.2% yield strength ratio is 0.990-0.083×(C%) or more.

[0058] The tensile strength, 0.2% yield strength ratio, and reduction in area of ​​the steel wire according to the present disclosure can be measured in accordance with the test method of JIS Z2241:2011 using a JIS Z2241:2011 No. 14A test piece, similar to the tensile test of the wire rod described above.

[0059] (Vickers hardness of steel wire) In the steel wire according to the present disclosure, the standard deviation of the Vickers hardness in a cross section (C cross section) perpendicular to the longitudinal direction of the steel wire is divided by the average Vickers hardness of 0.150 or less. If this value is 0.150 or less, the workability when forming into a mechanical part is improved, and the 0.2% proof stress ratio of the mechanical part is increased. The value is preferably 0.100 or less, and more preferably 0.050 or less. The hardness test of the steel wire can be carried out in the same manner as the hardness test of the wire rod described above, and the average value and standard deviation can be calculated in the same manner.

[0060] (Steel wire diameter) The wire diameter d of the steel wire according to the present disclosure is not particularly limited, but may be, for example, 2.0 to 23.0 mm, or 4.0 to 18.0 mm.

[0061] <Machine parts> The mechanical part according to the present disclosure is obtained by performing cold heading and rolling on the above-mentioned steel wire and processing it into the shape of a mechanical part such as a bolt. The mechanical part according to the present disclosure includes a shaft portion, and the shaft portion has the following metal structure and mechanical properties.

[0062] [Metal structure of shaft] When the diameter of the shaft is dm, the metal structure at a 1 / 4 dm portion, which is 1 / 4 dm deep from the surface of the shaft in a cross section (C cross section) perpendicular to the longitudinal direction of the shaft, contains bainite with an area ratio of 70% or more. If the bainite area ratio is less than 70%, the 0.2% proof stress ratio of the mechanical component decreases and workability deteriorates. The bainite area ratio is preferably 80% or more, and more preferably 90% or more. The metal structure of the shaft portion can be measured in the same manner as the metal structure of the wire rod described above.

[0063] [Mechanical properties of shaft] Tensile strength of shaft: 580+900×(C%)MPa or more In the mechanical component according to the present disclosure, the tensile strength of the shaft portion is 580+900×(C%) MPa or more, where (C%) is the C content in mass %, and the mechanical component exhibits high strength by having such a tensile strength.

[0064] 0.2% yield strength / tensile strength: 0.90 or more The mechanical component according to the present disclosure has a ratio of 0.2% proof stress to the tensile strength of the shaft (0.2% proof stress / tensile strength) of 0.90 or more. The mechanical component according to the present disclosure can obtain a high 0.2% proof stress ratio of 0.90 or more even without bluing treatment. The 0.2% proof stress / tensile strength is preferably 0.92 or more.

[0065] The tensile test can be performed using a linear test piece with the shaft cut off, in the same manner as in the tensile test of the wire described above, using a JIS Z2241:2011 No. 14A test piece, in accordance with the test method of JIS Z2241:2011.

[0066] (Vickers hardness of shaft) In the mechanical component according to the present disclosure, the standard deviation of the Vickers hardness in a cross section (C cross section) perpendicular to the longitudinal direction of the shaft portion is divided by the average value of the Vickers hardness, which is 0.150 or less. When this value is 0.150 or less, the 0.2% proof stress ratio of the mechanical component manufactured from the steel wire through wire drawing is high. In addition, the processability during molding into the mechanical component is improved. The value is preferably 0.100 or less, more preferably 0.050 or less. The hardness test of the shaft portion can be carried out in the same manner as the hardness test of the wire rod described above, and the method for determining the average value and standard deviation is also the same.

[0067] (shaft diameter) The diameter dm of the shaft portion of the mechanical component according to the present disclosure is not particularly limited, but may be, for example, 2.0 to 23.0 mm, or 4.0 to 18.0 mm.

[0068] (permanent set) The mechanical component according to the present disclosure has high 0.2% proof stress and suppressed permanent set. For permanent elongation, the shaft of the machine part is processed into a coarse thread shape by rolling or machining. After thread processing, an adapter specified in JIS B1051:2014 is attached to the machine part so that the length of the play thread is equal to the outer diameter of the thread. A tensile stress of 440 MPa when the tensile strength of the machine part is 600 MPa or more and less than 700 MPa, 515 MPa when the tensile strength is 700 MPa or more and less than 800 MPa, 580 MPa when the tensile strength is 800 MPa or more and less than 900 MPa, 650 MPa when the tensile strength is 900 MPa or more and less than 1000 MPa, 830 MPa when the tensile strength is 1000 MPa or more and less than 1100 MPa, 910 MPa when the tensile strength is 1100 MPa or more and less than 1200 MPa, 970 MPa when the tensile strength is 1200 MPa or more and less than 1300 MPa, and 1050 MPa when the tensile strength is 1300 MPa or more and less than 1400 MPa is applied in the axial direction for 15 seconds. The difference (L1-L0) between the total length L1 of the mechanical part after unloading and the total length L0 of the mechanical part before the test is defined as the permanent elongation. The total length L1 of the mechanical part after unloading and the total length L0 of the mechanical part before the test were measured using a micrometer. EXAMPLES

[0069] The wire according to the present disclosure will be described in more detail below with reference to examples, although the wire according to the present disclosure is not limited to these examples.

[0070] <Wire rod production and evaluation> Steels A to U having the chemical compositions shown in Table 1 were heated, hot rolled, cooled, and held under the conditions shown in Table 2 to produce wire rods. In Table 1, blanks indicate that the element was not included, and the balance is Fe and impurities. In each table, underlines indicate that the element is outside the scope of the present disclosure.

[0071] [Table 1]

[0072] [Table 2]

[0073] The obtained wires were subjected to microstructural observation, tensile testing, and hardness measurement by the methods described above. Table 3 shows the microstructural and mechanical properties of the wires of each test number. In Table 3, F in the remaining microstructural portion means ferrite, P means pearlite, and M means martensite.

[0074] [Table 3]

[0075] <Steel wire manufacturing> The wire rods in Table 3 were drawn at the area reduction rates shown in Table 4 to obtain steel wires. The obtained steel wires were subjected to the above-mentioned methods of microstructural observation, hardness measurement, and tensile testing in air at room temperature to measure tensile strength (TS) and reduction of area (RA). Steel wires with TS x RA of 52000 or more, TS of 610+900 x (C%) MPa or more, RA of 62-32 x (C%)% or more, 0.2% yield strength ratio of 0.985-0.083 x (C%) or more, and a value obtained by dividing the standard deviation of Vickers hardness by the average value of Vickers hardness of 0.150 or less were judged to have good strength, formability, and yield strength.

[0076] [Table 4]

[0077] <Bolt manufacturing> The steel wires in Table 4 were used and processed into bolt shapes by cold heading and rolling. Test numbers 1 and 13 had threads of M5 and shank lengths of 100 mm, test numbers 10 and 17 had threads of M6 and shank lengths of 100 mm, and test numbers 2 to 9, 11, 12, 14 to 16, 18 to 20, and 22 to 25 had threads of M8 and shank lengths of 100 mm. These were then electrogalvanized, and after plating, the bolts were baked at 200°C for 120 minutes to obtain bolts. Test number 21 cracked during bolt processing and could not be processed into a bolt shape. The bolt shafts were machined to obtain JIS Z2241:2011 No. 14A test pieces, and were measured according to the test method of JIS Z2241:2011. The diameter of the parallel part of the tensile test piece was 4 mm for the bolt with thread M5, 5 mm for the bolt with thread M6, and 7 mm for the bolt with thread M8. Tensile test pieces were taken and subjected to the above-mentioned methods of structure observation, hardness measurement, and tensile testing to measure the tensile strength (TS) and 0.2% proof stress. The 0.2% proof stress ratio of the bolt was calculated by dividing the 0.2% proof stress by the tensile strength. The bolts obtained were used to measure the permanent elongation according to the above-mentioned method. Table 5 shows the TS, 0.2% proof stress ratio, and permanent elongation of each bolt. It was judged as good when the TS was 580 + 900 × (C%) MPa or more, the 0.2% yield strength ratio (bolt yield strength ratio) was 0.90 or more, the value obtained by dividing the standard deviation of Vickers hardness by the average Vickers hardness was 0.150 or less, and the permanent elongation was 1 μm or less.

[0078] [Table 5]

[0079] From the above results, the wire rods and steel wires of test numbers 1 to 19 that satisfy the requirements of the present disclosure have excellent formability during bolt processing, and a high 0.2% yield strength ratio was obtained even without performing a bluing treatment after bolt processing.

[0080] (Additional Note) The present disclosure includes the following aspects. <1> Chemical composition, in mass%, C: 0.08 to 0.80%, Si: 0.03 to 1.50%, Mn: 0.50-2.00%, P: 0.050% or less, S: 0.050% or less, Al: 0.005 to 0.080%, N: 0.0010~0.0150%, O: Contains 0.003% or less, with the balance being Fe and impurity elements; When the diameter of the wire is D, a metal structure at a 1 / 4D portion having a depth of 1 / 4D from the surface of the wire in a cross section perpendicular to the longitudinal direction of the wire contains bainite at an area ratio of 70% or more, When the C content in mass% is (C%), the ratio of 0.05% proof stress to tensile strength (0.05% proof stress / tensile strength) is 0.72-0.40 × (C%) or more; A wire having a standard deviation of Vickers hardness in a cross section perpendicular to the longitudinal direction of the wire divided by the average value of the Vickers hardness of the wire, the standard deviation being 0.150 or less. <2> Chemical composition, in mass%, C: 0.08 to 0.80%, Si: 0.03 to 1.50%, Mn: 0.50-2.00%, P: 0.050% or less, S: 0.050% or less, Al: 0.005 to 0.080%, N: 0.0010~0.0150%, O: Contains 0.003% or less, and further contains one or more elements selected from the group consisting of the following A group to D group, with the balance being Fe and impurity elements, [Group A] Ti: 0.050% or less, and B: 0.0050% or less of one or two selected from the group consisting of [Group B] Cr: 1.50% or less, Mo: 0.50% or less Nb: 0.050% or less, and V: 0.20% or less, one or more selected from the group consisting of [Group C] Cu: 0.50% or less, Ni: 0.70% or less, Sn: 0.30% or less, and Sb: 0.005% or less, one or more selected from the group consisting of [Group D] Ca:0.0050% or less When the diameter of the wire is D, a metal structure at a 1 / 4D portion having a depth of 1 / 4D from the surface of the wire in a cross section perpendicular to the longitudinal direction of the wire contains bainite at an area ratio of 70% or more, When the C content in mass% is (C%), the ratio of 0.05% proof stress to tensile strength (0.05% proof stress / tensile strength) is 0.72-0.40 × (C%) or more; A wire having a standard deviation of Vickers hardness in a cross section perpendicular to the longitudinal direction of the wire divided by the average value of the Vickers hardness of the wire, the standard deviation being 0.150 or less. <3> Having a chemical composition containing the A group in mass%; <2> The wire material described in <4> Having a chemical composition containing the B group in mass%; <2> or <3> The wire material described in <5> Having a chemical composition containing the C group in mass%; <2> ~ <4> 13. The wire according to claim 12, <6> Having a chemical composition including the D group in mass%; <2> ~ <5> 13. The wire according to claim 12,

[0081] <7> Chemical composition, in mass%, C: 0.08 to 0.80%, Si: 0.03 to 1.50%, Mn: 0.50-2.00%, P: 0.050% or less, S: 0.050% or less, Al: 0.005 to 0.080%, N: 0.0010~0.0150%, O: Contains 0.003% or less, with the balance being Fe and impurity elements; When the diameter of the steel wire is d, a metal structure at a 1 / 4d portion having a depth of 1 / 4d from the surface of the steel wire in a cross section perpendicular to the longitudinal direction of the steel wire contains bainite in an area ratio of 70% or more, When the C content by mass is (C%), the tensile strength is 610+900×(C%)MPa or more, the reduction in area is 62-32×(C%)% or more, the tensile strength (MPa)×reduction in area (%) is 52000 or more, and the ratio of 0.2% proof stress to tensile strength (0.2% proof stress / tensile strength) is 0.985-0.083×(C%) or more, A steel wire, wherein a value obtained by dividing the standard deviation of Vickers hardness in a cross section perpendicular to the longitudinal direction of the steel wire by the average value of the Vickers hardness is 0.150 or less. <8> Chemical composition, in mass%, C: 0.08 to 0.80%, Si: 0.03 to 1.50%, Mn: 0.50-2.00%, P: 0.050% or less, S: 0.050% or less, Al: 0.005 to 0.080%, N: 0.0010~0.0150%, O: Contains 0.003% or less, and further contains one or more elements selected from the group consisting of the following A group to D group, with the balance being Fe and impurity elements, [Group A] Ti: 0.050% or less, and B: 0.0050% or less of one or two selected from the group consisting of [Group B] Cr: 1.50% or less, Mo: 0.50% or less Nb: 0.050% or less, and V: 0.20% or less, one or more selected from the group consisting of [Group C] Cu: 0.50% or less, Ni: 0.70% or less, Sn: 0.30% or less, and Sb: 0.005% or less, one or more selected from the group consisting of [Group D] Ca:0.0050% or less When the diameter of the steel wire is d, a metal structure at a 1 / 4d portion having a depth of 1 / 4d from the surface of the steel wire in a cross section perpendicular to the longitudinal direction of the steel wire contains bainite in an area ratio of 70% or more, When the C content by mass is (C%), the tensile strength is 610+900×(C%)MPa or more, the reduction in area is 62-32×(C%)% or more, the tensile strength (MPa)×reduction in area (%) is 52000 or more, and the ratio of 0.2% proof stress to tensile strength (0.2% proof stress / tensile strength) is 0.985-0.083×(C%) or more, A steel wire, wherein a value obtained by dividing the standard deviation of Vickers hardness in a cross section perpendicular to the longitudinal direction of the steel wire by the average value of the Vickers hardness is 0.150 or less. <9> Having a chemical composition containing the A group in mass%; <8> The steel wire according to claim 1. <10> Having a chemical composition containing the B group in mass%; <8> or <9> The steel wire according to claim 1. <11> Having a chemical composition containing the C group in mass%; <8> ~ <10> 2. The steel wire according to claim 1 . <12> Having a chemical composition including the D group in mass%; <8> ~ <11> 2. The steel wire according to claim 1 .

[0082] <13> A mechanical part including a shaft portion, Chemical composition, in mass%, C: 0.08 to 0.80%, Si: 0.03 to 1.50%, Mn: 0.50-2.00%, P: 0.050% or less, S: 0.050% or less, Al: 0.005 to 0.080%, N: 0.0010~0.0150%, O: Contains 0.003% or less, with the balance being Fe and impurity elements; When the diameter of the shaft portion is dm, a metal structure at a 1 / 4 dm portion having a depth of 1 / 4 dm from the surface of the shaft portion in a cross section perpendicular to the longitudinal direction of the shaft portion contains bainite in an area ratio of 70% or more, When the C content in mass% is (C%), the tensile strength of the shaft portion is 580 + 900 × (C%) MPa or more; The ratio of 0.2% proof stress to the tensile strength (0.2% proof stress / tensile strength) is 0.90 or more, A mechanical component, wherein a value obtained by dividing the standard deviation of Vickers hardness in a cross section perpendicular to the longitudinal direction of the shaft portion by the average value of the Vickers hardness is 0.150 or less. <14> A mechanical part including a shaft portion, Chemical composition, in mass%, C: 0.08 to 0.80%, Si: 0.03 to 1.50%, Mn: 0.50-2.00%, P: 0.050% or less, S: 0.050% or less, Al: 0.005 to 0.080%, N: 0.0010~0.0150%, O: Contains 0.003% or less, and further contains one or more elements selected from the group consisting of the following A group to D group, with the balance being Fe and impurity elements, [Group A] Ti: 0.050% or less, and B: 0.0050% or less of one or two selected from the group consisting of [Group B] Cr: 1.50% or less, Mo: 0.50% or less Nb: 0.050% or less, and V: 0.20% or less, one or more selected from the group consisting of [Group C] Cu: 0.50% or less, Ni: 0.70% or less, Sn: 0.30% or less, and Sb: 0.005% or less, one or more selected from the group consisting of [Group D] Ca:0.0050% or less When the diameter of the shaft portion is dm, a metal structure at a 1 / 4 dm portion having a depth of 1 / 4 dm from the surface of the shaft portion in a cross section perpendicular to the longitudinal direction of the shaft portion contains bainite in an area ratio of 70% or more, When the C content in mass% is (C%), the tensile strength of the shaft portion is 580 + 900 × (C%) MPa or more; The ratio of 0.2% proof stress to the tensile strength (0.2% proof stress / tensile strength) is 0.90 or more, A mechanical component, wherein a value obtained by dividing the standard deviation of Vickers hardness in a cross section perpendicular to the longitudinal direction of the shaft portion by the average value of the Vickers hardness is 0.150 or less. <15> Having a chemical composition containing the A group in mass%; <14> A mechanical part as described in. <16> Having a chemical composition containing the B group in mass%; <14> or <15> A mechanical part as described in. <17> Having a chemical composition containing the C group in mass%; <14> ~ <16> 2. A mechanical part according to claim 1 . <18> Having a chemical composition including the D group in mass%; <14> ~ <17> 2. A mechanical part according to claim 1 .

[0083] The disclosure of Japanese Patent Application No. 2023-059430, filed on March 31, 2023, is incorporated herein by reference in its entirety. All documents, patent applications, and technical standards described herein are incorporated herein by reference to the same extent as if each individual document, patent application, and technical standard was specifically and individually indicated to be incorporated herein by reference.

Claims

1. In mass percent, C: 0.08-0.80%, Si: 0.03 to 1.50%, Mn: 0.50-2.00%, P: 0.050% or less, S: 0.050% or less, Al: 0.005-0.080%, N: 0.0010-0.0150%, O: 0.003% or less, Ti: 0 to 0.050%, B: 0 to 0.0050%, Cr: 0-1.50%, Mo: 0 to 0.50%, Nb: 0 to 0.050%, V: 0 to 0.20%, Cu: 0 to 0.50%, Ni: 0 to 0.70%, Sn: 0 to 0.30%, Sb: 0 to 0.005%, and Ca: 0-0.0050%, and the balance being Fe and impurity elements, When a diameter of the wire is D, a metal structure at a 1 / 4D portion having a depth of 1 / 4D from a surface of the wire in a cross section perpendicular to a longitudinal direction of the wire contains bainite in an area ratio of 70% or more, When the C content in mass% is (C%), the ratio of 0.05% proof stress to tensile strength (0.05% proof stress / tensile strength) is 0.72-0.40×(C%) or more; A wire having a standard deviation of Vickers hardness in a cross section perpendicular to the longitudinal direction of the wire divided by an average value of the Vickers hardness of the wire, the standard deviation being 0.150 or less.

2. In mass percent, C: 0.08-0.80%, Si: 0.03 to 1.50%, Mn: 0.50-2.00%, P: 0.050% or less, S: 0.050% or less, Al: 0.005-0.080%, N: 0.0010-0.0150%, O: 0.003% or less, Ti: 0 to 0.050%, B: 0 to 0.0050%, Cr: 0-1.50%, Mo: 0 to 0.50%, Nb: 0 to 0.050%, V: 0 to 0.20%, Cu: 0 to 0.50%, Ni: 0 to 0.70%, Sn: 0 to 0.30%, Sb: 0 to 0.005%, and Ca: 0-0.0050%, and the balance being Fe and impurity elements, When the diameter of the steel wire is d, a metal structure at a 1 / 4d part having a depth of 1 / 4d from the surface of the steel wire in a cross section perpendicular to the longitudinal direction of the steel wire contains bainite in an area ratio of 70% or more, When the C content in mass% is (C%), the tensile strength is 610+900×(C%) MPa or more, the reduction in area is 62−32×(C%)% or more, the tensile strength (MPa)×reduction in area (%) is 52,000 or more, and the ratio of 0.2% proof stress to tensile strength (0.2% proof stress / tensile strength) is 0.985−0.083×(C%) or more, A steel wire, wherein a value obtained by dividing the standard deviation of Vickers hardness in a cross section perpendicular to the longitudinal direction of the steel wire by the average value of the Vickers hardness is 0.150 or less.

3. A mechanical part including a shaft portion, In mass percent, C: 0.08-0.80%, Si: 0.03 to 1.50%, Mn: 0.50-2.00%, P: 0.050% or less, S: 0.050% or less, Al: 0.005-0.080%, N: 0.0010-0.0150%, O: 0.003% or less, Ti: 0 to 0.050%, B: 0 to 0.0050%, Cr: 0-1.50%, Mo: 0 to 0.50%, Nb: 0 to 0.050%, V: 0 to 0.20%, Cu: 0 to 0.50%, Ni: 0 to 0.70%, Sn: 0 to 0.30%, Sb: 0 to 0.005%, and Ca: 0-0.0050%, and the balance being Fe and impurity elements, When the diameter of the shaft portion is dm, a metal structure at a 1 / 4 dm portion having a depth of 1 / 4 dm from a surface of the shaft portion in a cross section perpendicular to a longitudinal direction of the shaft portion contains bainite in an area ratio of 70% or more, When the content of C in mass% is (C%), the tensile strength of the shaft portion is 580 + 900 × (C%) MPa or more; The ratio of 0.2% proof stress to the tensile strength (0.2% proof stress / tensile strength) is 0.90 or more, A mechanical component, wherein a value obtained by dividing the standard deviation of Vickers hardness in a cross section perpendicular to the longitudinal direction of the shaft portion by the average value of the Vickers hardness is 0.150 or less.

Citation Information

Patent Citations

  • Non-refined steel material for weld bolt and method for producing the same

    JP2015190002A

  • Steel wire, wire for non-heat-treated mechanical components, and non-heat-treated mechanical component

    JP2021183710A

  • Wire material for non-refined machine component; steel wire for non-refined machine component; non-refined machine component; and method for manufacturing wire material for non-refined machine component, steel wire for non-refined machine component, and non-refined machine component

    WO2013031640A1

  • Rod material for non-tempered machine component, steel rod for non-tempered machine component, and non-tempered machine component

    WO2016121820A1

  • Steel wire for non-thermal-refined machine component, and non-thermal-refined machine component

    WO2017122830A1

Cited By

  • wire

    JP7904513B1

  • Wire rod

    WO2026154661A1